IN THIS ISSUE: Can the U.S. SNAP back? - Hilchey, Duncan (Journal of Agriculture, Food Systems, and Community Development, 2025)
First paragraphs: As I write, the U.S. federal government under the Trump administration has passed funding cuts to the Supplemental Nutrition Assistance Program (SNAP), which provides food benefits to people who are experiencing hunger—including children, seniors, people with disabilities, and others. This action is raising concerns about the potential reversal of gains in health outcomes since the program began, as well as the survival of nonprofit groups that have come to depend on the program for funding. If SNAP is to be maintained, states will need to fill any funding gap, meaning that fixed-income residents of poorer rural states are the most likely to feel the brunt of this policy and funding decision. In this issue, we publish a number of papers exploring the efficacy of SNAP. While there is always room for improvement, this research clearly demonstrates the program’s efficacy in staving off food insecurity. As the U.S. reimagines how it will support its vulnerable citizens, it is important to remind ourselves that a key measure of the strength of a nation is the quality of life for children and the elderly. Regardless of which level of government administers SNAP, we need to find a way to prevent the most vulnerable Americans from falling through the cracks. Reflecting his concerns about the direction the U.S. is headed in, our Economic Pamphleteer columnist John Ikerd calls for common sense in a time of uncertainty and encourages us to maintain our integrity as professionals studying and acting on the food system, with “truth and goodness guiding our actions.” Amen. . . .